If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -2 + 3n = -16 Reorder the terms: -2 + 4n + 3n = -16 Combine like terms: 4n + 3n = 7n -2 + 7n = -16 Solving -2 + 7n = -16 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7n = -16 + 2 Combine like terms: -2 + 2 = 0 0 + 7n = -16 + 2 7n = -16 + 2 Combine like terms: -16 + 2 = -14 7n = -14 Divide each side by '7'. n = -2 Simplifying n = -2
| 3(p+4)=12 | | (x+3)/(x+5)+(6)/(x^2+3x-10) | | 50=-16t^2+32t+50 | | 1/2-7/8 | | 0=x-2+4 | | 10x+27y-9=360 | | 10=-3p+p | | -9=4+5m+2 | | -3(x+5)=5(x+5) | | 9x^2-71x+56=0 | | 3x^3-27xy^2=0 | | -6(x+4)=-6(x+6) | | -3y+3+4y=-7 | | a+4=18 | | V-5v=-12 | | 45x+12-5=-21-(-52x) | | 12x^2+36xy=0 | | Log(2)(6x+9)=2 | | -6=-3x-3x | | 12=7x/3 | | N+3-3=-5 | | -2x-2y=28 | | -7x+96=5x | | 6=16t^2+22+6 | | -1.6(x+6)+1.4=4.6 | | 10x^2-15x/5x^2 | | (2x^2-3x+7)-(5x^2+3x+6)= | | h=16t^2+22+6 | | 18(r+t)=18r+18t | | H=50+32t+-16t^2 | | 2(x-y)=12 | | 1x+6=42 |